2020
DOI: 10.1177/0022243720940693
|View full text |Cite
|
Sign up to set email alerts
|

Construal Matching in Online Search: Applying Text Analysis to Illuminate the Consumer Decision Journey

Abstract: As consumers move through their decision journey, they adopt different goals (e.g., transactional vs. informational). In this research, the authors propose that consumer goals can be detected through textual analysis of online search queries and that both marketers and consumers can benefit when paid search results and advertisements match consumer search–related goals. In bridging construal level theory and textual analysis, the authors show that consumers at different stages of the decision journey tend to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 55 publications
(63 reference statements)
0
51
0
3
Order By: Relevance
“…Berger et al ( 2020 ), by analyzing social media posts created and shared during live political debates, found that tweets containing a more analytical language—but not authentic language style—were more likely to be shared after the debate. Humphreys et al ( 2020 ) found that consumers use more abstract (concrete) language in their online search during the first (last) stages of the shopping journey. Akpinar and Berger ( 2017 ) also suggest that highly arousing text ( tone ), both highly positive and highly negative, is more likely to be shared frequently and widely since the audience is more receptive to a message when it arouses affective states.…”
Section: Textual and Non-textual Cue Stimulating Retweetsmentioning
confidence: 99%
“…Berger et al ( 2020 ), by analyzing social media posts created and shared during live political debates, found that tweets containing a more analytical language—but not authentic language style—were more likely to be shared after the debate. Humphreys et al ( 2020 ) found that consumers use more abstract (concrete) language in their online search during the first (last) stages of the shopping journey. Akpinar and Berger ( 2017 ) also suggest that highly arousing text ( tone ), both highly positive and highly negative, is more likely to be shared frequently and widely since the audience is more receptive to a message when it arouses affective states.…”
Section: Textual and Non-textual Cue Stimulating Retweetsmentioning
confidence: 99%
“…Le tableau 3 mentionne les principales recherches fondées sur la théorie du fit pour prédire les effets positifs de l'adéquation entre les combinaisons haut niveau/éloignement et bas niveau/proximité. Cet ajustement entre niveaux de représentation et distance psychologique offre au consommateur une expérience subjective de fluidité de traitement de l'information (Humphreys et al, 2020 ;, qui a pour conséquence d'améliorer ses attitudes envers la publicité et la marque Spassova et Lee, 2013), son évaluation de la publicité (Roose et al, 2019 ;White et al, 2011), son intention d'achat et son consentement à payer un surprix pour l'offre proposée (Balbo et Jeannot, 2015).…”
Section: La Distance Psychologique Comme Variable Clé Pour Décrypter Les Phénomènes De Digitalisation De La Consommationunclassified
“…Niveau de concrétisation du langage (Humphreys et al, 2020) 1) Exposer la moitié des répondants à une modalité de la variable du mix étudié. Exposer l'autre moitié des répondants à l'autre modalité.…”
Section: Le Soiunclassified
“…Researchers (Ahuja, Gupta, & Raman, 2003;Albinsson et al, 2010;Humphreys et al, 2020;Liu et al, 2020;Nan, 2007;Williams & Bargh, 2008) examined how construal level influences consumers' purchasing decisions. For example, Albinsson et al (2010) studied effects of construal level on consumers' purchasing intention online and found consumers evaluated online products differently based on their inherent construal level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have studied what factors affect a consumer's purchasing decisions, and found that a consumer's inherent construal level affects a consumer's decision making (Albinsson et al, 2010;Kim & John, 2008). According to Construal Level Theory (CLT), people tend to interpret an event in a more abstract, goal oriented and general way when they are psychologically distant, whereas they interpret an event more concretely when the psychological distance is close (Humphreys, Isaac, & Wang, 2020;Liberman & Fo rster, 2009;Liberman & Trope, 2008;Liberman, Trope, & Stephan, 2007;Liu, Zhang, Huang, Zhang, & Zhao, 2020;Trope & Liberman, 2003).…”
Section: Introductionmentioning
confidence: 99%